Men's attitude and motivation toward consumption of grooming products: A comparison of Chinese and Pakistani male consumers - Imran Khan; Han Dongping; Muhammad Abdullah; Zeeshan Ahmad; Tauqir Ahmad Ghauri; Sidra Ghazanfar (Cogent Business & Management, 2017)
Current research explores the concept of masculine identity in modern social world as evidence of retail products consumption which was traditionally seen as female or feminine (cosmetic grooming products). This study comparatively analyze the effect of personal, social, and marketing factors on the attitude of Chinese and Pakistani male consumers toward the consumption of cosmetics. This paper begins with a comprehensive review of the literature on the topic. Data were collected from 260 Chinese and 210 Pakistani male customers from three metropolitan cities from each country. Descriptive statistics, correlation and regression analysis (ordinary least square (OLS) and Ridge) are used to test the hypotheses. Results show mixed effect on Chinese and Pakistani male's attitude and motivation toward consumption of cosmetic products. Physical attractiveness impacts only on Pakistani men while lifestyle effects only on Chinese male consumers. It directs the marketers to find the most significant factors toil in men cosmetic segment in China and Pakistan.
Keywords: 650